Impact of Celebrity Suicides on mental health of vulnerable population - Kumar, Santosh; Negi, Sapna (Indian Journal of Community Health, 2022)
Suicide is culminating into a grave public health concern. Approximately 800,000 people worldwide commit suicide annually, with 3/4th owing to low- middle-income countries.(1) In 2016, the suicide rate in India was 16.5, exceeding the global average of 10.5/1,00,000.(1) Suicide is the deliberate ending of one's own life(2) and primarily done due to persistent sense of despair, depression, drug misuse, and various personal and financial stress factors. One such trigger is suicide by an eminent figure, also known as werthering effect, modelling effect, or copycat suicide. This phenomenon commonly affects the adolescent and younger adults. In India, the 15-29 age group were found most vulnerable.(1) Nearly 5% of consecutive suicides occur after a celebrity death primarily among young, female, and unemployed without being prompted by adverse life circumstances.(3) Given the global gravity of suicide and India's contribution to it, it is critical to identify the psychopathology and risk factors behind it.